On the use of a personal or neutral tone in written feedback - Rachel Player (Journal of Learning Development in Higher Education)
It is well-known that the emotional response upon receiving feedback can impact how learners incorporate the comments received into their future learning. It is therefore essential that assessors consider the emotional impact of the feedback they provide. One aspect that may influence how the feedback is received is the style and tone of the feedback. This opinion piece introduces the explicit consideration of two styles of written feedback: personal (‘you show’) and neutral (‘the student shows’). Existing literature does not directly examine which (if either) of these styles can be considered as the most effective. I revisit the literature that investigates how the tone and style of feedback relates to the key features of effective feedback. Reflecting on each of the key features, I argue that adopting a personal tone is most natural. I also offer considerations for practice, highlighting that written feedback should be constructive, fair, and understandable, and delivered in a tone that is authentic to the personalities of both the educator and learner, to foster engagement and dialogue.